UPAYA PEMERINTAH KABUPATEN KEPULAUAN MERANTI DALAM PENYEDIAAN AIR BERSIH DI KECAMATAN TEBING TINGGI TAHUN 2012-2014 - Susanti, Dwi; Asrida, Wan (Nakhoda: Jurnal Ilmu Pemerintahan, 2016)
Government which includes local government (province/city/district) is a state organs thathas an authority in fulfilling its function to achieve its goals. The function of governmentincludes arrangement, development, empowerment and services. Those functions are inter-related, especially to assest the limitation to fulfill the availability of clean water in MerantiDistrict. This issue is already faced before the expansion of the district. The district belongs topeat area with the characteristic of dark red water in colour, thus force the local government toprovide clean water from the dark red water.